Catalytic meerwein-ponndorf-verley reductions over mesoporous silica supports: rational design of hydrophobic mesoporous silica for enhanced stability of aluminum doped mesoporous catalysts - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Samuel, Prinson R.; Srilakshmi, Ch; Singh, A. R. (Journal of Molecular Catalysis A-Chemical, 2009)
A series of aluminum isopropoxide-grafted mesoporous organosilica having ethane (-CH(2)-CH(2)-) and ethene (-CH=CH-) groups in the frame wall positions (ethane-silica, ethene-silica) as well as mesoporous silicas (MCM-41, MCM-48. SBA-15) through siloxide linkages were fabricated. The samples were used as catalysts in the Meerwein-Ponndorf-Verley reduction of ketones and aldehydes of different nature and size using secondary alcohols as the hydrogen transfer agents. Aluminum isopropoxide supported mesoporous silica samples show higher catalytic conversion and among them, the one-dimensionally channel oriented Si-MCM-41 supported aluminum isopropoxide shows better results than the three-dimensional Si-MCM-48 and the large pore Si-SBA-15. Compared to aluminum isopropoxide-grafted mesoporous silica samples, aluminum alkoxide-grafted organosilica samples shows better catalytic activity even in the presence of 10% of water and the better stability is attributed to the presence of integrated hydrophobic organic groups in the frame wall positions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aluminum isopropoxide; Mesoporous silica; Organosilica; reduction

Synthesis and characterization of bifunctional ethenylene bridged mesoporous organoaluminosilicates - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Srilakshmi, Ch.; Singh, A. P. (Nanoscience and Nanotechnology Letters, 2011)
Bifunctional mesoporous organosilicas having -CH=CH- bridges and aluminium in tetrahedral coordination with tailorable pore sizes have been synthesized using a one-step templating method using cationic surfactants of different chain lengths. Unlike the conventional EtOH-HCl template extraction process, EtOH-NH(4)NO(3) was used as the surfactant-extracting medium and chemical analysis results suggest that through this procedure the mesoporous structure can be retained and dealumination can be minimized. The surfactant-extracted mesoporous solids display high surface area, pore volume and the pore size of the material varies in the range 2.6-3.6 nm, with respect to the alkyl chain length of the cationic surfactant. XRD and nitrogen physisorption studies further proved that the organosilicas are hydro thermally stable than the conventional Al-MCM-41 materials and their better stability is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethenylene groups in the wall positions. The coupling of Al(4) with -CH=CH- bridges offer new prospects for the application of periodic mesoporous organosilicas in heterogeneous catalysis.
Keywords: Aluminium; Cationic Surfactants; Hydrothermal stability; Organosilicas